2003
DOI: 10.1074/jbc.m207264200
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor DNA Binding Is Required for Both Positive and Negative Gene Regulation

Abstract: The ␤ isoform of thyroid hormone receptor (TR-␤) has a key role in the feedback regulation of the hypothalamic-pituitary-thyroid (H-P-T) axis. The mechanism of trans-repression of the hypothalamic thyrotropin-releasing hormone (TRH) and pituitary thyroid-stimulating hormone (TSH) subunit genes, however, remains poorly understood. A number of distinct mechanisms for TR-␤-mediated negative regulation by thyroid hormone have been proposed, including those that require and do not require DNA binding. To clarify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 59 publications
3
80
0
4
Order By: Relevance
“…5). Gal4-NCoR, Gal4-SRC (LXXLL), and Gal4-SRC (q-rich) are able to bind to TR as expected (Christiaens et al 2002, Shibusawa et al 2003a, Iwasaki et al 2006) and this interaction is independent of an intact DBD of TR (Fig. 4B).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…5). Gal4-NCoR, Gal4-SRC (LXXLL), and Gal4-SRC (q-rich) are able to bind to TR as expected (Christiaens et al 2002, Shibusawa et al 2003a, Iwasaki et al 2006) and this interaction is independent of an intact DBD of TR (Fig. 4B).…”
Section: Discussionmentioning
confidence: 66%
“…4, all Gal4-cofactor fusion proteins were able to bind TR in a ligand-dependent manner. NCoR binds TR in the absence of T 3 whereas the SRC-1 binds TR in the presence of T 3 , as expected (Shibusawa et al 2003a). This binding is unaffected by point mutations within the DBD of TR, although the fold-repression ratesGT 3 are reduced compared with wild-type TR (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…S7A). In addition, we demonstrated that TET3 stabilized and promoted chromatin association of a TRα1 mutant (TRα1 G75S ) defective in DNA binding (15) as a result of a mutation in DNA binding domain (Fig. S7B).…”
Section: Discussionmentioning
confidence: 90%